2019
DOI: 10.1186/s13561-019-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of vertigo: a systematic review

Abstract: BackgroundVertigo, a highly prevalent disease, imposes a rising burden on the health care system, exacerbated by the ageing of the population; and further, contributes to a wide span of indirect burden due to reduced capacity to work or need of assistance in activities of daily living. The aim of this review was to summarise the evidence on the economic burden of vertigo.MethodsAll original studies published between 2008 and 2018 about the economic evaluation of peripheral or central vestibular vertigo in deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 59 publications
3
71
0
9
Order By: Relevance
“…Vertigo, a high frequency disease, imposes a rising burden on the health care system, aggravated by the aging of the population (1). Benign paroxysmal positional vertigo (BPPV) is the most common type of peripheral vestibular vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…Vertigo, a high frequency disease, imposes a rising burden on the health care system, aggravated by the aging of the population (1). Benign paroxysmal positional vertigo (BPPV) is the most common type of peripheral vestibular vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, routine data provided by the health insurer AOK Bayern will be linked to individual patient data from the trial. We will concentrate on outpatient visits, hospitalizations, visits to the emergency room, and imaging, because these seem to be the major cost drivers [26].…”
Section: Methodsmentioning
confidence: 99%
“…Balance disorders and consequent falls have progressively represented a burden of disease, accompanied by high costs and pressure on the social services and health care systems related to medical care. This includes repeated consultations, excessive use of diagnostic imaging, and emergency care [ 22 - 24 ]. For example, the first national study in the context of dizziness and vertigo in the Emergency Services of United States of America for 2011 revealed that 25.7% of patient complaints of dizziness and vertigo were associated with balance disorders.…”
Section: Introductionmentioning
confidence: 99%